Mengidentifikasi Dan Memaknai Paribasa Bali Pada Cerpen Gedè Ombak Gedè Angin Pupulan Sawelas Carita Cutet Basa Bali Karya I Made Suarsa - Ni Putu Swastini (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Paribasa is used in everyday life to convey the ideas and emotions of the Balinese people, as evidenced by the short narrative Gedé Ombak Gedé Angin by I Made Suarsa and other Balinese discourses. Furthermore, I Made Suarsa's short novel Gedé Ombak Gedé Angin employs Balinese paribasa to convey moral, ethical, and social critique principles that serve as a set of guidelines for daily life. The purpose of this study is to identify the various forms and interpretations of Balinese paribasa in I Made Suarsa's short novel Gedé Ombak Gedé Angin.The present study employs many theoretical frameworks, including the theories of identification, meaning, short stories, Balinese paribasa, and sorts of Balinese people. Using interviews and literature study techniques, this study is qualitative in nature. The study's findings indicate that: (1) There are two varieties of Balinese paribasa in the short narrative "Lahru Kangkang Tinibanin Udan Sawengi." (2) Three different kinds of Balinese paribasa are mentioned in the short novel "Gedé Ombak Gedé Angin" The short novella "Mati Maha Prawiréng Rana" features three distinct varieties of Balinese paribasa. The short novella "Stri Ngarania, Apuy Padania" features two distinct varieties of Balinese paribasa.included five interpretations of the Balinese paribasa in I Made Suarsa's short story Gedé Ombak Gedé Angin